Pengaruh Portal Pangkeptv Pada Penyebaran Informasi Terhadap Kepuasan Masyarakat Di Kecamatan Labakkang Kabupaten Pangkep - Shabirah , Nurafifah; Ahdan, Ahdan; Majid , Abdul (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
Media is a means of information for the community, where the media becomes a liaison or intermediary in providing information and conducting a communication. In the media is also very essential for society where the media and society are closely related and the media is the most important part in society. And without us realizing that the media provides positive and negative energy that has an impact on people's patterns and behavior. PangkepTV media as one of the media providing information to the Pangkep Community, makes researchers interested in knowing the level of community satisfaction in accessing the media. Based on that this research focuses on how the influence of PangkepTV on community satisfaction in the district. Labakkang, Pangkep Regency. The purpose of this study was to determine the management of the PangkepTV.pangkepkab.go.id portal in disseminating information and the influence of the information dissemination of the PangkepTV.pangkepkab.go.id portal on community satisfaction in the Labakkang District, Pangkep Regency. This research was conducted in Pangkep City, Labakkang District. The time of this research starts from May 2022. The research method used is quantitative method with descriptive research type. Using questionnaire data collection techniques. The results of this study indicate that the influence of the PangkepTV portal on the dissemination of information on public satisfaction can be concluded as follows, based on the results of a partial hypothesis test that the PangkepTV media variable has a positive and significant effect on community satisfaction in the Kanaungan sub-village, Labakkang District, Pangkep Regency and the PangkepTV media also has an effect on performance. government in disseminating information to the public so that people are satisfied in receiving information.